Huanuqueña music for saxophone learning at the National University “Daniel Alomía Robles” Huánuco – 2020 - Jorge Julca, Silverio L. (2022)
The present scientific article assumed the objective of determining the influence of huanuqueña music to saxophone learning in UNDAR students, Huánuco - 2020. The type, level and design used are: Applied and explanatory. The population was found to be made up of all the UNDAR students enrolled during the 2020 period, adding a total of 161 students from both faculties and the study sample was made up of 25 saxophone students, to whom an observation guide of 14 was applied questions about saxophone learning, where the degree of influence of huanuqueña music was evaluated to improve saxophone learning. The instrument used was the observation guide, which was validated by the judgment of qualified experts. Most of the participants evidenced an influence with respect to learning the saxophone, influenced by the application of huanuqueña music, the results show a significant improvement of 45.0% evidenced at the good level with respect to learning the saxophone in the UNDAR students after the application of huanuqueña music. The study shows that there is a significant improvement in saxophone learning in UNDAR students and this should be strengthened not only with music students but also with all university students in general to contribute to the improvement of learning at the national level.